Interest as Predictor of Mathematics Achievement among Senior Secondary School Students in Bida Educational Zone, Niger State, Nigeria - Ahmad , Manko Umar; Isa, Alhassan D.; Zakariyya, Aliyu A. (Journal of Instructional Mathematics, 2024)
This study investigates whether senior secondary school students' interest could predict their academic achievement in mathematics. A correlation research design was used with two research questions and one null hypothesis to guide the study. The target population encompassed 13866 students (9464 males and 4402 females) in SSSII across 46 senior secondary schools owned by the Niger state government, distributed within Bida educational zone spanning five local government areas. Using a multistage sampling method, a sample of 462 students (30% of the population) was selected. Two research instruments, (Mathematics Interest Scales [MIS] and Mathematics Achievement Test [MAT]) were validated with reliability coefficient (r=0.79 and 0.92). Data analysis was carried out using frequency, percentage, and Pearson Product-Moment Correlation (PPMC). The findings revealed that a significant portion of students had a low interest in mathematics, which was found to predict approximately 44% of the variations in academic achievement scores. Moreover, the study demonstrated a substantial relationship between students' interest in mathematics and their academic performance. These findings led to recommendations. Emphasizing perseverance in mathematics learning, teachers were encouraged to adopt innovative, learner-centric teaching strategies. Additionally, ensuring teacher motivation and support was deemed essential for assisting students in their mathematics education among others.